2010
DOI: 10.1002/elan.201000279
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Tryptophan at Gold Nanoparticle‐Modified Carbon Ionic Liquid Electrode

Abstract: The electrochemical behavior of tryptophan was studied at the carbon ionic liquid electrode (CILE) modified with gold nanoparticle (GNP). This electrode has a stable and excellent response toward tryptophan. Under optimum experimental conditions, the calibration curve was linear in the tryptophan concentration range of 5 to 900 mM with an excellent correlation coefficient (0.995). The experimental limit of detection was 4 mM. Contrary to many other electrodes, the oxidation of tryptophan on GNP/CILE does not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…Modification of the electrodes with mediators decreases working potential and improves performance of the sensor due to electrocatalytic effect and higher specific surface area. Thus, hemin , carbon nanotubes , ferrocene , Au nanoparticles , acetylene black , taken alone or in combination and included in electropolymerized matrices have been successfully used in the assembly of voltammetric sensors for the Trp determination. Although many of the above sensors show excellent sensitivity, the deposition of the sensing layer often involves several steps with rather complicated intermediate treatment of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the electrodes with mediators decreases working potential and improves performance of the sensor due to electrocatalytic effect and higher specific surface area. Thus, hemin , carbon nanotubes , ferrocene , Au nanoparticles , acetylene black , taken alone or in combination and included in electropolymerized matrices have been successfully used in the assembly of voltammetric sensors for the Trp determination. Although many of the above sensors show excellent sensitivity, the deposition of the sensing layer often involves several steps with rather complicated intermediate treatment of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical performance of PDA-β-CD-GCE has been compared with other reported electrodes and the results are shown in Table 1 [27][28][29][30][31][32][33][34][35][36][37][38]. Binuclear manganese (II) complex modi ied CPE requires 60.0 s accumulation times prior to the determination of Trp and moreover, the energy required to oxidize Trp at this electrode was more as compared to PDA-β-CD-GCE [28].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation overpotential at expensive BDD NWs [36] was very high and it required a highly basic medium for the electrocatalytic oxidation of Trp. A two-step procedure was involved in the preparation of GNP/ CILE [37]. The PDA-β-CD-GCE has certain advantages as compared to glassy carbon (GC) electrode modi ied with MWCNTs; GC/MWCNT [38].…”
Section: Resultsmentioning
confidence: 99%
“…To make a distinct comparison with previous literature reported methods, the characteristics of different electrochemical sensors for tryptophan are shown in Table 1. [37][38][39][40][41][42][43][44][45][46] This indicated that the SC4A and cysteamine modified gold electrode was an appropriate platform for the electrochemical determination of tryptophan and had higher sensitivity to tryptophan (Table 1). Figure 9 shows that SC4A had the highest interaction with tryptophan in three SCnA (n = 4, 6, 8).…”
Section: Tryptophan−sc4a Interactionmentioning
confidence: 94%